Polyurethane foams based on modified tung oil and reinforced with rice husk ash II: Mechanical characterization - Ribeiro Da Silva, Virginia (2013)
Viscoelastic polyurethane (PU) foams based on modified tung oil, ethylene glycol and polymeric MDI, and reinforced with rice husk ash (RHA), were prepared by a free-rise pouring method and characterized in terms of density, compression and dynamic mechanical behavior. The density of foams ranged between 50 and 90 kg/m3, depending on the position of the sample with respect to the foam rise direction and filler content. As revealed by dynamic mechanical tests, the foams exhibited two different and broad thermal transitions, the temperature of their maxima depending on filler concentration. Compression modulus, compressive strength and storage modulus increase as foam density increases but decreases as rice husk ash concentration increases due to the detrimental changes induced by the filler in the foam cellular structure. However, densification strain exhibits the opposite behavior, indicating that reinforced foams can sustain slightly higher deformations without collapsing, probably due to a reduced reactivity of the components induced by the filler. © 2013 Elsevier Ltd. All rights reserved.